Understanding degradation mechanisms of perovskite solar cells due to electrochemical metallization effect - Wang, Hai Qiao; Wang, Sunan; Chen, Lijun; Yin, Zhipeng; Mei, Sikai; Zhong, Ying; Yao, Yirong; Li, Ning; Wang, Jianhao; Song, Weijie (Solar Energy Materials and Solar Cells, 2021)
Operational stability is becoming one of the most crucial parameters for commercialization of perovskite solar cells (PSCs). However the stability issue of PSCs is currently far from being resolved due to complicated and still unclear degradations. In this work, we systematically demonstrate the degradation of metal cathode PSCs under operation conditions. Discussions about influence of intrinsic factors i.e. light illumination, voltage and current, on device degradation are conducted. It is concluded that metal cathode stripping/plating behavior (electrochemical metallization effect) due to current together with perovskite degradation could dominate the device degradation. It is deduced that electrochemical cell in the PSC system could be formed by metal/counter electrodes and perovskite electrolyte. Both cells accelerate degradation of metal electrode and perovskite in working conditions, hence device degradation. These insights into the degradation and mechanisms can help further understand the working principle and solve the instability problem of perovskite-based optoelectronic devices.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Electrochemical metallization effect; Metal electrode; Perovskite solar cell; Stability